Perbandingan Struktur dan Kinerja Pasar Modal Serta Pasar Uang Indonesia dan Arab Saudi: Analisis Deskriptif-Komparatif - Try Maya Andira; Maryam Batubara (Economic Reviews Journal, 2026)
This study aims to compare the structure and performance of capital markets and money markets in Indonesia and Saudi Arabia as two countries with large Muslim populations and rapidly developing Islamic finance industries, yet with differing economic structural characteristics. The research employs a descriptive-comparative approach using secondary data sourced from the Indonesia Stock Exchange (IDX), Saudi Exchange (Tadawul), Bank Indonesia (BI), the Saudi Central Bank (SAMA), the Financial Services Authority (OJK), and official institutional publications for the 2024-2026 period. The analysis covers four main dimensions: market capitalization and number of listed issuers, money market instrument structure and monetary policy, Islamic financial instrument development, and the conformity of both markets with Maqashid Syariah principles. The findings indicate that Tadawul possesses a significantly larger capital market capitalization than IDX, driven by the dominance of the energy sector and a single mega-issuer (Saudi Aramco), while IDX demonstrates faster retail investor base growth and broader sectoral diversification. On the money market side, both countries rely on interest-based monetary operation instruments (BI-Rate/SRBI in Indonesia, SAMA's repo rate in Saudi Arabia), which conceptually still require further development of more comprehensive sharia-compliant instruments. Indonesia is recorded as one of the largest global sukuk issuers after Saudi Arabia and Malaysia, indicating potential synergy and benchmarking opportunities between the two countries. This study recommends strengthening bilateral cooperation in developing Islamic money market instruments and harmonizing sharia governance standards across capital markets.